The dynamics of the floodwater and the damaged ship in waves - 高志亮 VASSALOS Dracos (Journal of hydrodynamics. Series B, 2015)
The interaction between the dynamics of the floodwater and the damaged ship in waves is investigated by applying an integrated method, which couples a seakeeping solver and a Navier-Stokes solver. To reveal the effects of the water flooding and the sloshing on the damaged ship behaviour, the motion of a Ro-Ro ferry in regular beam seas is simulated, including the ship under the intact condition with and without internal water and the ship under a damaged condition. It is found that the shift of the natural roll frequency of a damaged ship and the decrease of its roll response are mainly due to the water sloshing inside the compartment. The effect of the resonant sloshing leads to the presence of a ship＇s second peak response at higher frequencies and it is significantly reduced by the water flooding through the damaged opening. The influence of the flooding and the sloshing on the ship behaviour is small with a further increase of the wave frequency.